Pendidikan Islam Berbasis Kearifan Lokal: Strategi Penguatan Identitas Keislaman di Era Globalisasi - Agung Supriadi; Dinda Ayu Maulila Ramadhani; Is Nainila Nur Syahfitri (Institut Agama Islam Uluwiyah Mojokerto Indonesia, 2026)
Islamic education based on local wisdom is an approach that integrates Islamic teachings with the cultural values and traditions of the local community. This concept aims to form individuals who not only have intellectual intelligence, but also have noble character, responsibility, and have a strong understanding of Islam in their cultural context. Local wisdom such as mutual cooperation, deliberation, and religious traditions can enrich the implementation of Islamic teachings in daily life. The integration of local wisdom in Islamic education plays a role in preserving culture and strengthening students' Islamic identities to be more tolerant and respectful of diversity. In the era of globalization, Islamic identity faces challenges due to the influence of westernization, secularization, and modernization that can erode traditional and religious values. The crisis of Islamic identity, especially among the younger generation, is increasing due to the influence of social media and lifestyles that are not always in line with Islamic teachings. Therefore, Islamic education has an important role in strengthening Islamic identity by adopting strategies based on local wisdom. The main strategy in strengthening Islamic identity through Islamic education based on local wisdom includes the development of a curriculum that integrates cultural values in Islamic religious learning and contextual learning methods. This approach ensures that Islamic values can be internalized effectively through a familiar environment for learners. Thus, Islamic education not only functions as a means of religious learning, but also as a medium for cultural preservation that is in line with Islamic values. The integration of local wisdom in Islamic education is a strategic step in creating a generation of Muslims with strong character, adhering to Islamic teachings, and being able to face the challenges of globalization without losing their Islamic identity.